Giant lobular capillary hemangioma of the breast - Assogba Léopold Azakpa; Essodina Ndayake; Irene Gonzalez-Rodilla; Florent Priuli (Elsevier, 2019)
Lobular capillary hemangioma or pyogenic granuloma is a benign vascular tumor of the skin or mucous membranes characterized by rapid growth and friable surface. It occurs at any age. The etiology remains unclear. We report the case of a 9-month-old girl with ulcerated breast mass which bleeds easily since two months with anemia. In fear of a malignant tumor, complete surgical removal of all breast tissue was performed successfully. Histopathologic study of the surgical specimen concluded to giant lobular capillary hemangioma with healthy borders. The infant is recurrence free at 6 months of follow up. Giant lobular capillary hemangioma of the breast with ulceration and easily bleeding may be mistaken for malignancy tumor. Keywords: Breast, Lobular capillary hemangioma, Surgery